2011
DOI: 10.1542/peds.2010-1218
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Fever Syndromes in Patients After Recovery From Kawasaki Syndrome

Abstract: The recurrence of fever in a child with a history of Kawasaki syndrome (KS) poses a dilemma for clinicians who must consider the possibility of recurrent KS. In this report we present the cases of 4 patients who presented with classical symptoms of KS, were successfully treated with intravenous immunoglobulin, and later experienced a reappearance of inflammatory symptoms in a pattern consistent with a recurrent fever syndrome. The association of these syndromes within the same patient suggests that some patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Broderick et al . reported that four children with a history of KD developed PFAPA . They noted that the incidence of four patients with PFAPA (4.7%) among 84 KD patients in San Diego County, seemed to be higher than expected, because the morbidity of PFAPA was estimated to be 9–34 in 100 000 children younger than 18 years.…”
Section: Discussionmentioning
confidence: 98%
“…Broderick et al . reported that four children with a history of KD developed PFAPA . They noted that the incidence of four patients with PFAPA (4.7%) among 84 KD patients in San Diego County, seemed to be higher than expected, because the morbidity of PFAPA was estimated to be 9–34 in 100 000 children younger than 18 years.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported the clinical presentation of systemic onset juvenile arthritis after the KD diagnosis and noted on literature review of prior reported cases that most were diagnosed as incomplete KD specifically lacking scleral injection [4]. Mevalonate kinase deficiency and PFAPA diagnoses causing recurrent fevers have been previously described after initial treatment for incomplete KD [10,11]. Whether children who were subsequently diagnosed with an autoimmune/autoinflammatory illness actually had KD initially or had an alternative diagnosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether children who were subsequently diagnosed with an autoimmune/autoinflammatory illness actually had KD initially or had an alternative diagnosis is unclear. It has been suggested that recurrent fever disorders and KD may share the same propensity for activation of innate immune responses causing elevations in cytokine profiles and that the diseases may be related in those predisposed [11]. In either case, clinicians should observe these children for development of other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While both the innate and acquired systems are activated after pathogen infection, clinical and laboratory studies have found that the occurrence of KD is related to the activation of the innate immune system (Hara et al, 2016). Lori Broderick et al reported 4 cases of KD with the reoccurrence of inflammatory clinical symptoms similar to those in "recurrent fever syndrome" existed in febrile disease due to the dysregulation of innate immune system (Broderick et al, 2011). The acquired immune system has both cell-mediated immunity and humoral immunity.…”
Section: Immunopathogenesis Of Kdmentioning
confidence: 99%